16. SURVEY OF THE SITUATION CARE OF MULTIPLE MYELOMA PATIENTS TREATED WITH BORTEZOMIB REGIMENS (Vietnam Journal of Community Medicine, 2025)
Objectives: To evaluate the current status of care for multiple myeloma patients treated with bortezomib-containing chemotherapy regimens at the Hematologic Oncology Department, K Hospital.Subjects and methods: A prospective descriptive study conducted on 76 Multiple myeloma patients received bortezomib-containing regimens at Hematologic Oncology Department, K Hospital from May 2019 to October 2022.Results: Mean age was 58.76; Male/female ratio 0.9; The majority of patients admitted to the hospital with PS=1 status accounted for 40.8%; the proportion of PS 2-4 patients accounted for 27.5%; Main symptom was bone pain, accounting for 84.2%; The rate of good basic care reached 56.6%; The group of patients with good care reduces the risk of side effects with p
Keywords: Multiple myeloma; Caregiving